Analisis Prosedur Penyusunan Anggaran Operating Cost The Reiz Suites Artotel Curated Medan - Emi, Emilia Contesa Lubis; Tambun, Rosmaida (Jurnal Akuntansi, Keuangan dan Perpajakan, 2024)
This study aims to analyze the operating cost budgeting procedure at The Reiz Suites Artotel Curated Medan. The study was conducted using a case study method to deeply understand the budgeting process at the hotel. Primary data was obtained through interviews with financial managers and related staff, while secondary data was obtained from the company's internal documentation. Analysis was carried out on the stages of budgeting, factors that influence cost estimates, and cost control strategies implemented by management. The results of the study obtained include factors that influence the preparation of the operating cost budget at The Reiz Suites Artotel Curated Medan, namely internal factors, which include price estimates taken from digital marketing and the determination of the company's revenue target must increase but still with excellent service, as well as external factors that include competitive conditions in facilities in the hotel industry which are increasingly increasing. Keywords: Budgeting, Procedures, Operating Costs   Abstrak Penelitian ini bertujuan untuk menganalisis prosedur penyusunan anggaran operating cost pada The Reiz Suites Artotel Curated Medan. Penelitian dilakukan dengan metode studi kasus untuk memahami secara mendalam proses penyusunan anggaran di hotel tersebut. Data primer diperoleh melalui wawancara dengan manajer keuangan dan staf terkait, sedangkan data sekunder diperoleh dari dokumentasi internal perusahaan. Analisis dilakukan terhadap tahapan penyusunan anggaran, faktor-faktor yang memengaruhi estimasi biaya, serta strategi pengendalian biaya yang diterapkan oleh manajemen. Hasil penelitian yang diperoleh antara lain faktor-faktor yang mempengaruhi penyusunan anggaran operating cost The Reiz Suites Artotel Curated Medan adalah faktor internal, yang meliputi estimasi harga diambil dari digital marketing serta penetapan target revenue perusahaan harus meningkat namun tetap dengan excellent service, serta faktor eksternal yang meliputi kondisi persaingan dalam fasilitas pada industri perhotelan yang semakin meningkat Kata Kunci: Anggaran, Prosedur, Biaya Operasional